Sistem Pengairan Otomatis Pada Media Tanaman Hias Menggunakan Sensor Soil Moisture Berbasis Web (Studi Kasus: Ebenbena Flora) - Devi Yunita; Dani Muliansyah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Soil is one of the growing media for plants, both annual crops and annual plants for humans and other living things. The body of soil consisting of air (20-30%), air (20-30%), mineral matter (45%), and organic matter (5%) is very dynamic in nature, that is, it continuously experiences changes influenced by climate (rainfall). . and temperature), shape of the area (relief or shape of the land surface), parent material, time, and organisms. The purpose of this research was to be able to make a tool that can water plants automatically using WEB which later, if this research is successful, it is hoped that with this tool humans will no longer need to water plants manually. In writing and conducting this research, the authors used the waterfall as a method for designing an automatic watering system on WEB-based ornamental plant media. The essence of the waterfall method is the work of a system that is carried out sequentially. Based on the results and discussion in the previous chapter, it can be concluded that this research has produced Automatic irrigation system for ornamental plant media. Used to monitor the irrigation of ornamental plants automatically based on the setting of the soil moisture value with the help of a soil moisture sensor. With a system made by ornamental plant owners, they can monitor plant humidity by viewing real-time sensor data on the system created so that plants do not lack or excess water.